2019
DOI: 10.1016/j.sjopt.2019.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Tarsal-related cysts: Different diagnoses with similar presentations

Abstract: PurposeTo study different tarsal cysts that share similar presentations and are commonly misdiagnosed clinically as a chalazion.MethodsA retrospective review of medical charts of all consecutive patients who presented eyelid tarsal-related pathology that needed surgical excision between 2010 and 2016 to a tertiary hospital was done. The data collected included preoperative, intraoperative and postoperative observations. Complete ophthalmologic examination at presentation, surgical procedures needed, complicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…Twelve case reports 1,2,4–13 and 6 case series were included. 3,14–18 The largest series outlined 15 cases of TEC. 14 The mean age of all patients was 52.3 years (range 18–85 years), with 50.8% being female.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve case reports 1,2,4–13 and 6 case series were included. 3,14–18 The largest series outlined 15 cases of TEC. 14 The mean age of all patients was 52.3 years (range 18–85 years), with 50.8% being female.…”
Section: Resultsmentioning
confidence: 99%
“…The true incidence of IKCs is also unknown. However, it has been suggested that these lesions represent the third leading cause of tarsal-related pathologies, after chalazia and sebaceous gland carcinoma [ 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, the lesions present as a small, non-inflammatory nodule, firm upon palpation and fixed to the tarsus, but with freely movable overlying skin on the upper eyelids of middle-aged male adults [ 3 , 6 ]. Although rare, multiple IKCs associated with the Gorlin–Goltz syndrome (GGS) have been reported [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With an understanding of ocular embryology, Williams et al reviewed the published literature on torpedo maculopathy and speculate that this lesion develops from a congenital nerve fiber layer-driven mechanism 2 . Similarly, meticulous synthesis of the clinical and pathologic features of corneal opacification in acquired corneal subepithelial hypertrophy by Al-Rajhi et al 3 , of the various etiologies of tarsal cysts by Al Rubaian et al 4 , and of challenging inflammatory juvenile conjunctival melanocytic nevi by Nebot et al 5 will expand our understanding of these diseases.…”
mentioning
confidence: 99%